Chronic stress-induced synaptic changes to corticotropin-releasing factor-signaling in the bed nucleus of the stria terminalis - Maita, Isabella; Roepke, Troy A.; Samuels, Benjamin A. (Frontiers in Behavioral Neuroscience, 2022)
The sexually dimorphic bed nucleus of the stria terminalis (BNST) is comprised of several distinct regions, some of which act as a hub for stress-induced changes in neural circuitry and behavior. In rodents, the anterodorsal BNST is especially affected by chronic exposure to stress, which results in alterations to the corticotropin-releasing factor (CRF)-signaling pathway, including CRF receptors and upstream regulators. Stress increases cellular excitability in BNST CRF+ neurons by potentiating miniature excitatory postsynaptic current (mEPSC) amplitude, altering the resting membrane potential, and diminishing M-currents (a voltage-gated K+ current that stabilizes membrane potential). Rodent anterodorsal and anterolateral BNST neurons are also critical regulators of behavior, including avoidance of aversive contexts and fear learning (especially that of sustained threats). These rodent behaviors are historically associated with anxiety. Furthermore, BNST is implicated in stress-related mood disorders, including anxiety and Post-Traumatic Stress Disorders in humans, and may be linked to sex differences found in mood disorders.